Ternary organic solar cells: compatibility controls for morphology evolution of active layers. Issue 41 (11th October 2017) - Ai, Qingyun; Zhou, Weihua; Zhang, Lin; Huang, Liqiang; Yin, Jingping; Yu, Zoukangning; Liu, Siqi; Ma, Wei; Zeng, Jianrong; Chen, Yiwang
Abstract : Compatibility between components described by Flory–Huggins parameters controls morphology evolution in ternary organic solar cells. Abstract : The fundamental principles of how a third component influences morphology evolution in ternary solar cells remains poorly understood. Here, P3BT, P3HT, and P3OT with different side chain lengths were incorporated into a p -DTS(FBTTh2 )2 :PC71 BM system to investigate the morphology evolution of films from a single component to binary blend films and from binary to ternary blend films. The compatibility between different components determined the final morphology of active layers during film formation, which could be described by Flory–Huggins parameters calculated through a melting point depression method. P3BT could promote crystallization of p -DTS(FBTTh2 )2 in ternary blends to afford an optimized morphology, reaching a maximum power conversion efficiency (PCE) of 7.3% after further annealing treatment.